PRIMA1 mutation: a new cause of nocturnal frontal lobe epilepsy. Issue 8 (3rd July 2015) - Hildebrand, Michael S.; Tankard, Rick; Gazina, Elena V.; Damiano, John A.; Lawrence, Kate M.; Dahl, Hans‐Henrik M.; Regan, Brigid M.; Shearer, Aiden Eliot; Smith, Richard J. H.; Marini, Carla; Guerrini, Renzo; Labate, Angelo; et al.
Abstract Objective Nocturnal frontal lobe epilepsy (NFLE) can be sporadic or autosomal dominant; some families have nicotinic acetylcholine receptor subunit mutations. We report a novel autosomal recessive phenotype in a single family and identify the causative gene. Methods Whole exome sequencing data was used to map the family, thereby narrowing exome search space, and then to identify the mutation. Results Linkage analysis using exome sequence data from two affected and two unaffected subjects showed homozygous linkage peaks on chromosomes 7, 8, 13, and 14 with maximum LOD scores between 1.5 and 1.93. Exome variant filtering under these peaks revealed that the affected siblings were homozygous for a novel splice site mutation (c.93+2T>C) in the PRIMA1 gene on chromosome 14. No additional PRIMA1 mutations were found in 300 other NFLE cases. The c.93+2T>C mutation was shown to lead to skipping of the first coding exon of the PRIMA1 mRNA using a minigene system. Interpretation PRIMA1 is a transmembrane protein that anchors acetylcholinesterase (AChE), an enzyme hydrolyzing acetycholine, to membrane rafts of neurons. PRiMA knockout mice have reduction of AChE and accumulation of acetylcholine at the synapse; our minigene analysis suggests that the c.93+2T>C mutation leads to knockout of PRIMA1. Mutations with gain of function effects in acetylcholine receptor subunits cause autosomal dominant NFLE. Thus, enhanced cholinergic responses are the likely cause of the severe NFLE and intellectual disability segregating in this family, representing the first recessive case to be reported and the first PRIMA1 mutation implicated in disease.